1979
DOI: 10.1017/s002510030000195x
|View full text |Cite
|
Sign up to set email alerts
|

The epiglottis as an articulator

Abstract: We believe that the importance of the epiglottis in speech has been generally underestimated in the phonetic literature. Our evidence leads us to conclude that the epiglottis is an active and independent articulator in the production of pharyngeal consonants and that it is involved in the production of the vowel [a] and in whisper. In earlier phonetic works that we have examined, to the extent that the epiglottis is mentioned at all, it is generally said to have no speech function. An exception to this is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Laufer and Condax (1979) observed the epiglottis with a fiberscope during the production of pharyngeals by Sephardic Hebrew 5 speakers and concluded that the epiglottis was retracting independently of the tongue root. Against this, Boff Dkhissi (1983, cited by Butcher and Ahmad (1987)) concluded on the basis of a cinefluorographic investigation of Moroccan Arabic that both tongue root and epiglottis were involved.…”
Section: X2 Gutturals Within Distinctive Feature Theory X21 the Armentioning
confidence: 99%
“…Laufer and Condax (1979) observed the epiglottis with a fiberscope during the production of pharyngeals by Sephardic Hebrew 5 speakers and concluded that the epiglottis was retracting independently of the tongue root. Against this, Boff Dkhissi (1983, cited by Butcher and Ahmad (1987)) concluded on the basis of a cinefluorographic investigation of Moroccan Arabic that both tongue root and epiglottis were involved.…”
Section: X2 Gutturals Within Distinctive Feature Theory X21 the Armentioning
confidence: 99%
“…Second, if, as commonly suggested in the literature, /ʕ/ involves more than one constriction, then perceptual nasalisation may result from the creation of a laryngeal sub-cavity. Such cavity can be created in at least two ways: (a) through actions of the epiglottis: here, the tip of the epiglottis forms a complete closure with the back of the pharyngeal wall (Laufer and Condax, 1979;1981;MacCurtain;1981) and the base of the epiglottis forms a constriction with the aryepiglottic folds (Esling 2005;Heselwood, 1997;Laver, 1980;Zeroual et al, 2008). The varying degree of constriction also explains the inconsistent patterns found in this study; if there is only narrow constriction between the tip of the epiglottis and the posterior pharyngeal wall, no tight cavity is formed; (b) through actions of the tongue and larynx: here, the root of the tongue may also retract towards the mid-pharyngeal, the larynx may raise for efficient laryngeal sphinctering (Esling, 2005;MacCurtain, 1981), and the glottis may form a complete closure for a glottal stop (Al-Ani, 1970).…”
Section: Comparing Nasalisation Results For the Voiced And The Voicelmentioning
confidence: 99%
“…The earliest phonetic description of pharyngeals in Arabic probably dates back to the seminal work of Sibawayh in the 8 th century, who identified the middle of the throat as the place of articulation of these sounds (Sibawayh 1966). More precisely, pharyngeals are produced with a constriction in the lower pharynx with the involvement of two main articulators: the tongue root and epiglottis (Laufer andCondax 1979, El-Halees 1985;McCarthy 1994). However, using laryngoscopic analysis, Esling (1996Esling ( , 1999 points out that the articulation of pharyngeals involves a constriction of the aryepiglottic folds.…”
Section: The Phonetic Properties Of Pharyngealsmentioning
confidence: 99%